Investigation on thermal stability of Si0.7Ge0.3/Si stacked multilayer for gate-all-around MOSFETS. (24th September 2020) - Cheng, Xiaohong; Li, Yongliang; Wang, Guilei; Liu, Haoyan; Zan, Ying; Lin, Hongxiao; Kong, Zhenzhen; Zhong, Zhaoyang; Li, Yan; Wang, Hanxiang; Xu, Gaobo; Ma, Xueli; et al.
Abstract: In this study, the thermal stability of a Si0.7 Ge0.3 /Si stacked multilayer for gate-all-around (GAA) MOSFETS is systematically investigated. Rapid thermal annealing (RTA) treatments at temperatures ranging from 800 °C to 1050 °C are performed on the Si0.7 Ge0.3 /Si stacked multilayer samples. Compared with the as-grown sample, the RTA-treated (800 °C–900 °C) Si0.7 Ge0.3 /Si stacked multilayer samples attain good crystal quality, a sharp interface between Si0.7 Ge0.3 and Si, and minor diffusion of Ge. Furthermore, owing to the rapid diffusion of Ge, the thickness of Si0.7 Ge0.3 increases by ∼6 nm and the Ge concentration of Si0.7 Ge0.3 reduces by ∼3% as the annealing temperature increases to 950 °C. The interfaces of the Si0.7 Ge0.3 /Si stacked multilayer disappear and finally behave like a homogeneous SiGe alloy as the annealing temperature further increases to 1000 °C or 1050 °C. Therefore, for thermal stability, the highest tolerable temperature of 900 °C is proposed for the Si0.7 Ge0.3 /Si stacked multilayer for the fabrication of the GAA device.